2020
DOI: 10.1155/2020/3646423
|View full text |Cite
|
Sign up to set email alerts
|

Variable Load Demand Scheme for Hybrid AC/DC Nanogrid

Abstract: This paper addresses the use of nanogrid technology in resolving the issue of blanket load shedding for domestic consumers. This is accomplished by using different load management techniques and load classification and utilizing maximum solar energy. The inclusion of DC-based load in basic load and DC inverter load in regular load and scheduling of the burst load during the hours of maximum solar PV generation bring novelty in this work. The term “nanogrid” as a power structure remains ambiguous in various pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Load shedding for domestic users is quite common in rural areas, the scheme is developed for load management for PV system for maximum power utilization [19]. Sun irradiance and temperature are the main dependents for maximum PV power output, due to variations in both PV system is considered to be nonlinear.…”
Section: Design Of Photovoltaic Systemmentioning
confidence: 99%
“…Load shedding for domestic users is quite common in rural areas, the scheme is developed for load management for PV system for maximum power utilization [19]. Sun irradiance and temperature are the main dependents for maximum PV power output, due to variations in both PV system is considered to be nonlinear.…”
Section: Design Of Photovoltaic Systemmentioning
confidence: 99%
“…As a result, hardware tests using the solar panel, AC‐grid, and batteries as the power sources proved that the controller operated properly. Rauf et al 97 discussed the use of AC/DC nano‐grid technology in resolving the question of blanket load shedding for domestic consumers. Numerical results showed that real‐time pricing is more economically viable than flat‐rate tariff for a house without DG, whereas flat‐rate configurations are more beneficial when DG is involved in nano‐grids.…”
Section: Applications Of Hybrid Ac/dc Power Distribution and Mgmentioning
confidence: 99%